The impact of cross-language phonological overlap on bilingual and monolingual toddlers’ word recognition* - VON HOLZEN, KATIE (Biling (Camb Engl), 2018)
We examined how L2 exposure early in life modulates toddler word recognition by comparing German–English bilingual and German monolingual toddlers’ recognition of words that overlapped to differing degrees, measured by number of phonological features changed, between English and German (e.g., identical, 1-feature change, 2-feature change, 3-feature change, no overlap). Recognition in English was modulated by language background (bilinguals vs. monolinguals) and by the amount of phonological overlap that English words shared with their L1 German translations. L1 word recognition remained unchanged across conditions between monolingual and bilingual toddlers, showing no effect of learning an L2 on L1 word recognition in bilingual toddlers. Furthermore, bilingual toddlers who had a later age of L2 acquisition had better recognition of words in English than those toddlers who acquired English at an earlier age. The results suggest an important role for L1 phonological experience on L2 word recognition in early bilingual word recognition.